Saberes-práticas docentes sobre crianças em situação de dificuldades na aprendizagem da leitura e da escrita do 5º ano do ensino fundamental de Fortaleza - Santana, Juliana Silva (2022)
The study aims to analyze the teaching knowledge-practices about children in situations of difficulties in learning reading and writing in the 5th grade of Elementary School. We rely theoretically on Vigotski's socio-historical Psychology (2007, 2009, 2018); on Kleiman (2007; 1995), on Solé (1998) and on Street (2014) to support discussions on literacy and reading/writing; on Tardif (2014), Charlot (2013, 2002, 2000) and Lustosa (2009, 2021), discussions on teaching knowledge-practices and on Patto (2015) and Charlot (2002), reflections on learning difficulties. This is a qualitative research, crossed by the complex context of the COVID-19 pandemic, involving a pilot study (face-to-face) evaluating the reading and writing of children in a public school in Fortaleza; the application of a questionnaire (online) with teachers of the 5th year of the municipal school system of Fortaleza and the realization of a collaborative stage from a course (online) offered to teachers of the 5th year of the public and private networks of Fortaleza, using as didactic-methodological procedures the life histories of teachers, teaching cases, among others. The data were analyzed using the Meaning Nuclei (AGUIAR; OZELLA, 2013; AGUIAR; BOCK, 2016). The results showed that: i. Students named as having "difficulties in learning reading and writing” are those who do not meet the crystallized expectations of teachers and the formal curriculum of the school grade which, in turn, are the students who are still at initial levels of the acquisition of this process; ii. Teachers' practical knowledge involving reading/writing, literacies and possible difficulties in this learning are not always interrelated in the classroom, even though they know that such processes have implications for each other and that they should be given in a planned, intentional and articulated way to the daily lives of apprentices, especially when it comes to students who have more difficulties in this learning; iii. The supports offered by teachers to children in situations of reading and writing difficulties, in general, do not correspond to the levels of help demanded by them, since mediation only happens "when it counts". In this case, students experiencing some difficulties in the learning dimension would need closer and more constant mediation to build their learning. Teachers point out that this "disconnection" between knowledge-practice occurs mainly because of the gap between the curriculum of the school grade and the prescribed contents and those that they believe are feasible for the learning of this group of students. It also emerges from the teachers' reports that external pressures (especially related to assessments) influence their practices, in addition to the erroneous idea that, in order to include these students and make them literate, specific knowledge is needed, a differentiated and adapted mediation and/or practices that they are not able to guarantee and that they do not know or cannot perform. Teachers simplify activities, impoverish the curriculum for them, disconnecting them from classroom experiences, and yet they are anxious and anxious that students' learning develops at the level expected for 5th grade.